Meningkatkan Keterampilan Reading For Comprehension Melalui Metode Learning Together - Riamawati, Dina (STKIP PGRI Ponorogo Press, 2021)
The purpose of this study is to improve students’ reading for comprehension skill using Learning Together method. This study uses a classroom action research design (action research) by applying three cycles. Each cycle consists of four stages, namely: planning, acting, observing, and reflectiing. The subjects of this study are Class XII (IPS-1) SMA Negeri 1 Sampung, Ponorogo with a total of 23 students. The research is carried out in the odd semester of the 2020/2021 academic year. Data were collected through document study (daily test results), observation and tests. Data are analyzed using interactive models (Miles and Hubberman) and descriptive statistics. From the results of the analysis, it is known that students’ reading for comprehension skills have increased from cycle I to cycle III, as follows; cycle I (60.86%), cycle II (73.39%), and cycle III (95.65%). Based on the result of analysis, the researcher concludes that Learning Together method can improve the students’ reading for comprehension skill, reflected in the result of each cycle. Empirically, the Learning Together method can be used as an alternative method in learning English that is applicable.